Disinfection and in vitro establishment of Acacia mearnsii nodal segments - Salles, Ecléia Alexandra Poltronieri Buda (2017)
Due to low rates of rooting it is difficult to propagate selected clones of Acacia mearnsii by cuttings. The purpose of this study was to define a protocol for disinfection of nodal segments for in vitro introduction, aiming to improve the species genetically for forest plantation. Combination of different products concentration (70% ethyl alcohol, sodium hypochlorite, plant preservative mixture and mercuric chloride), immersion period and size of nodal segment were tested. The best disinfection treatment was the combination of 70% ethanol, 0.4% mercuric chloride, sodium hypochlorite at 2% in nodal segments of 10 mm, with 80% survival.